Facing a Stormy Night Experiences of Campus Journalists Who Championed the Press Conference (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2026)
Campus journalism is a training ground for students to become skilled writers and open-minded citizens. In addition, it teaches them to become resilient as they are expected to face challenges and overcome them through the campus journalism exposure they receive, including their participation in journalistic competitions. This study explored the experiences of campus journalists who won first place in their respective categories during a journalistic competition. This study utilized a qualitative research design through transcendental phenomenology as the researchers focused on describing what the informants experienced. The researchers interviewed four high school campus journalists of Union Christian College students who won first place in the Divisions Schools Press Conference (DSPC) 2023. Unstructured interview was used to gather the data which was then thematically analyzed. Their experience is symbolically interpreted as an individual facing a stormy night, where the informants face challenges as they prepare for their competition, and how they cope with and overcome the challenges. The first theme “upcoming storm” revealed how the informants faced challenges including unfamiliarity as they will be competing for the first time since the pandemic (an unknown phenomenon), transitioning to a new category different from their previous journalistic experience (a new experience), mental and emotional difficulties (fearing the unknown), and short time for preparation (storm’s nearing approach). The second theme “preparing for the storm” reveals how they faced the challenges they met as they approach the journalistic competition. The informants ensured that they are updated to any current events that may come out during the contest (an informed citizen). They also participated eagerly in all the training sessions offered to them (preparing for the tempest). Furthermore, they associate their school as a nurturing ground for aspiring campus journalism champions (a sturdy house). The findings indicate that campus journalists face inevitable challenges before any journalistic competition but are driven to overcome them to become champions. Future studies may look into the experiences of other winning and non-winning campus journalists to have a deeper sense of their experiences when facing campus journalism competitions.
Keywords: campus journalism; campus journalists; journalistic experiences